Раскройте скобки и упростите выражение : (1) 5(а + 2b - 3) - 4 * (b - a - 4) (2) 7(2x - y...

0 голосов
32 просмотров

Раскройте скобки и упростите выражение : (1) 5(а + 2b - 3) - 4 * (b - a - 4) (2) 7(2x - y - 4) - 3 (5x - 3y - 9) (3) 11(k - 3n + 8) - 3 * (4k - 11n + 27) Помогите пожалуйста,буду очень благодарна))


Алгебра (184 баллов) | 32 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

 (1) 5(а + 2b - 3) - 4 * (b - a - 4) = 5a +10b -15 -4b+4a+16 = 9a +6b +1
(2) 7(2x - y - 4) - 3 (5x - 3y - 9) = 14x -7y -28 -15x +9y +27 = -x +2y -1
(3) 11(k - 3n + 8) - 3 * (4k - 11n + 27) = 11k -33n +88 - 12k +33n - 81 = -k +7


(28.2k баллов)
0 голосов

1) 5a+10b-15-4b+4a+16=9a+6b+1
2) 14x-7y-28-15x+9y+27=-x+2y-1
3)11k-33n+88-12k+33n-88=-k

(240 баллов)
0

в отпечатка 11k-33n+88-12k+33n-81=-k+7